Volatile HRS asymmetry and subloops in resistive switching oxides. Issue 38 (18th September 2017) - La Torre, Camilla; Kindsmüller, Andreas; Wouters, Dirk J.; Graves, Catherine E.; Gibson, Gary A.; Strachan, John Paul; Williams, R. Stanley; Waser, Rainer; Menzel, Stephan
Abstract : A volatile effect in non-volatile ReRAM memories that leads to a current asymmetry and the occurrence of subloops is presented. Abstract : Current–voltage characteristics of oxide-based resistive switching memories often show a pronounced asymmetry with respect to the voltage polarity in the high resistive state (HRS), where the HRS after the RESET is more conducting than the one before the SET. Here, we report that most of this HRS asymmetry is a volatile effect as the HRS obtained from a read operation differs from the one taken from the switching cycle at identical polarity and voltages. Transitions between the relaxed and the volatile excited states can be achieved via voltage sweeps, which are named subloops. The excited states are stable over time as long as a voltage is applied to the device and have a higher conductance than the stable relaxed state. Experimental data on the time and voltage dependence of the excitation and decay are presented for Ta/TaO x /Pt and Ta/ZrO x /Pt devices. The effect is not limited to one oxide or electrode material but is observed with different magnitudes (up to 10× current change) in several oxide systems. These observations describe an additional state variable of the memristive system that is controlled in a highly polarity dependent manner.